Inside Front Cover: A rapid differential display analysis of nasal swab fingerprints to distinguish allergic from non‐allergic rhinitis subjects by mesoporous silica particles and MALDI‐TOF mass spectrometry. Issue 6 (March 2017) - Lombardo, Nicola; Preianò, Mariaimmacolata; Maggisano, Giuseppina; Murfuni, Maria Stella; Messina, Luigi; Pelaia, Girolamo; Savino, Rocco; Terracciano, Rosa
Abstract : DOI:10.1002/pmic.201600215 The cover highlights the peptidomics‐based platform developed by our group to capture naturally occurring circulating peptides acting as messengers in the control of various biological processes in particular, in the field of allergy. The cover shows different MALDI‐TOF profiles generated from nasal swabs of a healthy, an allergic and three non‐allergic subjects with different cytologic phenotypes. These rhinomic fingerprints extrapolated by our tool might in the future be able to reveal a distinctive pattern of molecular features correlated by specific relative expression in each analyzed subject, with the hope of providing a more practical route to personalized treatment. For more details, see the research article by Nicola Lombardo et al., article number 1600215.